2021
DOI: 10.1039/d1ob00816a
|View full text |Cite
|
Sign up to set email alerts
|

5-Nitroisoxazoles in SNAr reactions: access to polysubstituted isoxazole derivatives

Abstract: An efficient protocol for straightforward functionalization of isoxazole ring via the reactions of aromatic nucleophilic substitution of nitro group with various nucleophiles has been elaborated. The method is featured with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The mechanism for the reaction is analogous to the one presented by Averina et al [22] . It is anticipated that the formation of a new C−S bond and the C−NO 2 bond breaking occurs in a concomitant fashion (see Scheme 1 in SI).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The mechanism for the reaction is analogous to the one presented by Averina et al [22] . It is anticipated that the formation of a new C−S bond and the C−NO 2 bond breaking occurs in a concomitant fashion (see Scheme 1 in SI).…”
Section: Resultsmentioning
confidence: 66%
“…The scalability of the reaction was tested by reacting 1 ac and 1 ae with thiol 2 c and it was observed that though the solid products 3 acc and 3 aec separated from the reaction mixture, the yields were marginally lower. The mechanism for the reaction is analogous to the one presented by Averina et al [22] It is anticipated that the formation of a new CÀ S bond and the CÀ NO 2 bond breaking occurs in a concomitant fashion (see Scheme 1 in SI).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In particular, the structures containing the phenylene-based linkers and aminoisoxazole moieties were identified among the most promising potential PAMs. Recently, we have elaborated a novel preparative method for the synthesis of 3-EWG-5-nitroisoxazoles, based on the heterocyclization of electrophilic alkenes via treatment with the tetranitromethane-triethylamine (TNM-TEA) complex [36][37][38][39]. Until now, this method has been used to produce polysubstituted isoxazoles containing one heterocyclic fragment in a molecule.…”
Section: Chemistrymentioning
confidence: 99%